p-STATISTICAL CONVERGENCE OF ORDER a IN PROBABILITY - Akbas, Kubra elif; Isik, Mahmut (Yokohama Publ, 2024)
In this study, we introduce and examine the concepts of p-statistical convergence of order alpha in probability and strong p-summability of order alpha in probability. We give some relations related with to these concepts.
Keywords: Statistical convergence; random variables; Cesaro summability; statistical convergence in probability